THE CURATOR'S AUTHORITY TO MANAGE AND CONTROL THE ASSETS OF THE "BANKLE DEBTOR" - Zulpahmi Harahap; Fitri Rafianti (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In the decision to declare bankruptcy, a Curator and a Supervisory Judge must be appointed from among the Court judges. Bankruptcy Law and postponement of debt payment obligations Article 69 number 1 regulates that the Curator's task is to manage and/or settle bankrupt assets, there is no further explanation regarding what is meant by "management of bankrupt assets" or "clearance of bankrupt assets". The formulation of the research problem is how the curator's duties and authority are regulated based on the Bankruptcy Law and whether in carrying out these duties and authority the curator is obliged to obtain approval from the supervising judge. The aim of this research is to find out the duties and authority of the curator and whether or not the curator needs the approval of the supervising judge to carry out his duties. The method used in this research is normative legal research with a statutory approach, a conceptual approach. The results of the analysis in the Bankruptcy Law and the postponement of debt payment obligations regulate the duties and authority of the curator, however there are several articles which regulate that the duties or authority of the curator require approval from the supervisory judge and other articles regarding the duties or authority of the curator are not clearly regulated whether the curator In carrying out their duties, the approval of the supervising judge is required.